ISOLATION AND IDENTIFICATION OF TERPENOID COMPOUNDS FROM n-HEXANA EXTRACT OF PERMOT PLANT BRACTS (Passiflora foetida L) - Maria Dewi Astuti; Tuti Sriwinarti; Kamilia Mustikasari (Program Studi Kimia, Universitas Lambung Mangkurat, 2017)
Isolation and identification of terpenoids compounds from n-hexane extract of permot bracts plants (Passiflora foetida L.) has been done. Crude powder of the bracts permot plants were macerated with n-hexane. Fractionated of n-hexane extract on a vacuum liquid chromatography to afford three fractions (A, B and C). Purification of fraction B with TLC preparative to afford isolate B1 and B2.. A compound of spectra UV-Vis B1 indicating the presence of conjugation of double bond (C=C), furthermore the IR spectra showed vibration for - OH group, C=O of the ester group, C-O group, and methyl group (-CH3) in position gem dimethyl. 1H-NMR spectra showed the signal from methoxy group (OCH3), olefin protons (-CH=CH-), protons in carbon to the oxygenation (C-OH), two units gem dimethyl, and three methyl group (-CH3). 13C-NMR spectra showed thesignal from carbon aliphatic group, carbon carbonil (C=O) of the ester group, double bond carbon (C=C), and carbon to the oxygenation (C-OCH3 and C-OH)). Based on the analysis of UV-Vis, IR, 1H-NMR, and 1H-NMR spectrocopies data, isolate B1 is suggested from terpenoids type triterpenoids pentacyclic that conjugation of double bond and ester group.Keywords: Terpenoids, triterpenoids pentacyclic, permot (Passiflora foetida L.), and n-hexane extract.